Evaluation of Blood C Reactive Protein (CRP) and Neutrophil-to-Lymphocyte Ratio (NLR) Utility in Canine Epilepsy - Andreea Despa; Mihai Musteata; Gheorghe Solcan (Veterinary Sciences)
Background: The role of neuroinflammation in epileptogenesis has been previously explored, and several biomarkers have been identified as being relevant in assessing the intensity of the inflammatory process. In human medicine, an increased C reactive protein (CRP) blood concentration and/or neutrophil-to-lymphocyte ratio (NLR) is considered a constant finding of epileptic activity. In veterinary medicine, only a few studies have been published regarding both of these topics. Hypothesis/objectives: Our aim was to assess the C reactive protein blood concentration and the neutrophil-to-lymphocyte ratio in epileptic dogs, regardless of etiology. Method: This retrospective study was based on changes in routine blood parameters in 59 dogs with epileptic activity. Results: An increased C reactive protein concentration was observed mostly in the dogs affected by structural epilepsy, and all epileptic dogs displayed abnormal neutrophil-to-lymphocyte values. Conclusions: Based on the authors’ knowledge, this is the first report regarding the NLR in epileptic dogs. Both the CRP concentration and the NLR might be considered feasible non-specific markers of the neuroinflamation involved in epileptogenesis and might be used in the diagnosis of and therapeutic approach to cluster seizures in dogs with idiopathic epilepsy and in patients with structural epilepsy. Dogs diagnosed with IEis and high CRP concentrations and NLRs may be subject to non-documented cluster seizures. Both CRP and the NLR have limited diagnostic value in dogs with reactive seizures.